Medium-scale measurement campaign for floating macroplastic detection in a realistic environment at x-band frequencies - Vala, M.; Felício, J.; Costa, T.; Leonor, N.; Costa, J. R.; Marques, P.; Moreira, A. A.; Matos, S.; Caldeirinha, R.; Fernandes, C. A.; Fonseca, N. J. G.; Maagt, P. (EuCAP 2025: 19th European Conference on Antennas and Propagation, 2025)
In this paper we assess the possibility of detecting floating plastics in a medium-scale realistic environment using microwave (MW) and RADAR technology at X-band. The measurement campaign performed in the “25 de Abril” bridge over the Tagus River allowed for distances of around 100 m between the antennas and the targets. Several different targets with sizes of 1m2 were tested and detected. The use of objective metrics also allowed to see which of the targets presented a higher response. This is an encouraging step towards the implementation of such detection techniques onboard drones or airplanes.